Changes in self-perceived willingness to communicate during visits to Second Life: a case study. Issue 2 (4th March 2021) - Kruk, Mariusz
ABSTRACT: The present paper presents the results of a study which examined the changes in the levels of willingness to communicate (WTC) in the virtual world of Second Life (SL) reported by a single student of English philology in 19 sessions spanning the period of one semester, and the factors accounting for such fluctuations. Using data gathered by means of a set of collection instruments (i.e. a background questionnaire, Learning Styles Survey, a session log and a semi-structured interview), the study found that the student's WTC underwent some changes both during her visits to SL and from one session to the next. These ups and downs in WTC levels were affected by a host of positive (e.g. friendly and willing to talk interlocutors, interesting topics, the shielding effect of avatar, confidence in using English) and negative (e.g. the lack of SL users willing to talk, the experience of boredom, group conversations) factors.